2018
DOI: 10.1016/j.smr.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Sport participation: From policy, through facilities, to users’ health, well-being, and social capital

Abstract: Sport delivery systems, aimed at facilitating sports participation, represent an interinstitutional, cross-sector collaboration. Researchers focusing on the impact of different levels of sport provision from policy, through facilities, to end users remains limited. The authors address this gap in knowledge through a mixed-methods approach to examine sport participation from the perspective of the whole delivery system. Specifically, focusing on a County Sport Partnership region in the UK, the authors examine s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 62 publications
2
36
0
1
Order By: Relevance
“…The most scientific and robust evidence relates to health, where there is consensus that participation in sport and physical activity generates population-wide primary (preventative) and secondary (therapeutic) physical and mental health benefits. This includes the prevention and treatment of chronic diseases including, but not limited to, cardiovascular disease, strokes, diabetes, obesity, some cancers, various neurological conditions and clinical depression (Allender et al, 2007;Kumar et al, 2018;Warburton et al, 2006Warburton et al, , 2007. The dose response relationship is complex and varies by disease (Davies et al, 2019).…”
Section: Social Impact Of Sportmentioning
confidence: 99%
See 2 more Smart Citations
“…The most scientific and robust evidence relates to health, where there is consensus that participation in sport and physical activity generates population-wide primary (preventative) and secondary (therapeutic) physical and mental health benefits. This includes the prevention and treatment of chronic diseases including, but not limited to, cardiovascular disease, strokes, diabetes, obesity, some cancers, various neurological conditions and clinical depression (Allender et al, 2007;Kumar et al, 2018;Warburton et al, 2006Warburton et al, , 2007. The dose response relationship is complex and varies by disease (Davies et al, 2019).…”
Section: Social Impact Of Sportmentioning
confidence: 99%
“…There is also significant evidence that engagement in sport and physical activity through participation and volunteering can have a positive effect on the subjective wellbeing of individuals. Research suggests that active people are generally more satisfied and happier than those that are physically inactive (Downward & Rascuite, 2011;Fujiwara et al, 2014a;Kumar et al, 2018;Rasciute & Downward, 2010). While this evidence tends to be based on analysis of large secondary cross-sectional datasets, regression analysis is commonly used with an instrumental variable approach to establish causal evidence of a relationship between sport and subjective well-being (Fujiwara et al, 2014a;Ruseski et al, 2014;Wicker & Downward, 2019).…”
Section: Social Impact Of Sportmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeking a wider range of outcomes through sport-based interventions and establishment of partnerships with non-sport sectors is characteristic of policy aspirations internationally (e.g. Grix & Carmichael, 2012;Kumar et al, 2018;Lyras & Welty-Peachey, 2011;Mansfield, 2016;Skinner, Zakus, & Cowell, 2008;Trendafilova, Ziakas, & Sparvero, 2017;Weed, 2016;Weed et al, 2015;Ziakas, 2015). This special issue, triggered by the thematic problematics emerging from the UK Sport Development Network (UKSDN) 2017 conference, seeks to uncover the global challenges in terms of managing the re-orientation of stakeholder activities and organisational strategies in response to re-alignments of sport policy.…”
Section: Purpose and Scopementioning
confidence: 99%
“…But in a study by Vandermeerschen and Scheerder (2016), in the deprived areas, the condition of sports and sports facilities is undesirable and there is a need for the cooperation of sports managers and local authorities to develop sports in these areas (16). Pitts and Shapiro (2017) also emphasized the importance of equitable distribution of sports supplies for the sport of the disabled and its role in the development of sport tourism (1), and Kumar et al (2018) also considered sports participation to be dependent on the distribution of facilities, welfare and social capital (17). Fereydouni et al (2015) also showed that in Iran large provinces have more sporting events and more investment in sports by the private sector with higher levels of sports success and more facilities than population (18).…”
Section: Introductionmentioning
confidence: 99%